Pulmonary Tuberculosis and Lepromatous Leprosy Coinfection - F. A. Sendrasoa; I. M. Ranaivo; O. Raharolahy; M. Andrianarison; L. S. Ramarozatovo; F. Rapelanoro Rabenja (Hindawi Limited, 2015)
Simultaneous occurrence of leprosy and pulmonary tuberculosis is reported infrequently in the modern era. We report a case of pulmonary tuberculosis diagnosed in patient being treated with glucocorticoids for complications of leprosy (type II reaction). Physicians should recognize that the leprosy patients treated with glucocorticoid may develop tuberculosis.